People Habitus and Sustainability Through Reading Literature After the COVID-19 Pandemic - Sekartaji, Maya; Ayienda Dinanti, Putri; Yunanda Damanik, Firly (KnE Social Sciences, 2023)
The world has suffered from COVID-19 since 2020. The high rate of death happens everywhere. In addition, nearly all sectors of life have been destroyed, which leads to chaotic situations. Suddenly people have to be able to survive in many ways. Not only must they get through death, but mentally as well. It is the moment when people express how they feel in literary works to balance their emotions with their mental states. This paper aims to describe the impact of the COVID-19 pandemic on particular social groups through reading literary works, and how these literary works can positively change people who survived when the pandemic occurred. Qualitative research is the method used in this paper. On employing Habitus theory from Pierre Bordieu on selected fields, media, and practices, we found that some people tend to read literature more during pandemics. They choose the pandemic topic, neither the classic nor the newest literature readings. Having read specific readings, they find salvation and form a sense of hope in dealing with the outbreak. This paper results that through rigorous literature reading, habitus is formed to ensure sustainability post-pandemic (COVID-19). Keywords: habitus, sustainability, reading literature, post-pandemic